Dynamics of cholera epidemics in the African great lakes region: case of the Democratic Republic of Congo - (:unkn) unknown (My University, 2009)
Cholera is a contagious diarrhoeal disease affecting only human, caused by Vibrio cholerae, a gram-negative bacillus. The disease results in profuse watery diarrhoea sometimes accompanied by vomiting, occurring after a few hours or a few days after the ingestion of food or water soiled by V. cholerae. In the environment, Vibrio cholerae is found in brackish water of estuarine zones where it colonizes the surface of algae and copepods, persisting in the absence of men for prolonged periods of time. So is the situation in the estuarine zones of South-East Asia such as the Bay of Bengal where the disease is known since the highest antiquity. After having been relatively spared by the first six pandemics, continental Africa was stroke in 1970 by the spread of the 7th pandemic of cholera. Since this date, according to the World Health Organization (WHO), more than 90 % of the cases of cholera were reported by Sub-Saharan African countries. Among them, the Democratic Republic of Congo (DRC) is one of the most affected countries. In DRC, from 2000 to 2008, 208,875 cases and 7,335 deaths (case fatality rate: 3.51 %) of cholera were reported to WHO, that is to say about 15 % of the cases and 20 % of the deaths observed worldwide during the same period. These cholera cases were mostly notified in the provinces of the East of the DRC, next to the African Great Lakes area. After more than 30 years of fight against cholera in DRC, an epidemiological study of the dynamics of cholera was set up in this country in order to better understand the epidemic factors of recurrence and to perform adjustments for the operational approaches. The main results of this research work have highlighted that less than 10 % of the health zones, all bordering lakes located in the East of the DRC, play the role of sanctuary zones for cholera. These results have also highlighted the seasonal variations of cholera, with fewer cases during the dry season, and the specific role of the fishe
Keywords: African Research